Bridging the Digital Divide: Empowering Teachers with AI Tools in Rural Indonesian Schools - Rulyansah, Afib; Ghufron, Syamsul; Akhwani, Akhwani; Rihlah, Jauharotur; Hardiningrum, Andini; Mustofa, Mustofa; Retikasari, Frysca Virnanda (Indonesia Berdaya, 2025)
The integration of artificial intelligence (AI) in education has the potential to revolutionize teaching and learning, particularly in under-resourced areas. This community service project aimed to empower 20 primary school teachers in Kecamatan Yosowilangun, Lumajang, with the skills and knowledge to integrate AI tools into their instructional practices. Over a six-month period, the project provided a series of workshops, hands-on training, and ongoing support to enhance teachers’ digital literacy and confidence in using AI. The results demonstrated significant improvements in both teacher competency and student engagement. Post-training surveys revealed that teachers' confidence in using AI tools for classroom management, lesson planning, and grading increased from an average of 2.1 (pre-training) to 4.3 (post-training) on a five-point Likert scale. In-class observations indicated that AI-powered platforms such as Google AI and Scratch enhanced student motivation and personalized learning, leading to a 20% improvement in test scores. However, the project also identified challenges, including limited technological infrastructure, teacher resistance, and disparities in student access to devices. These findings underscore the need for continued professional development, investment in technology infrastructure, and policy support to ensure the sustainability of AI integration in education. This study contributes to the growing body of research on AI in education by providing insights into the practical implementation of AI tools in rural schools. The success of this project highlights the transformative potential of AI for improving educational equity and empowering teachers in under-resourced settings.